SAFE@HOME – Feasibility study of a telemonitoring platform combining blood pressure and preeclampsia symptoms in pregnancy care. (September 2019) - van den Heuvel, Josephus F.M.; Kariman, Shariva S.; van Solinge, Wouter W.; Franx, Arie; Lely, A. Titia; Bekker, Mireille N.
Abstract: Objective: To study the feasibility of a telemonitoring platform for hypertensive disease in pregnancy, consisting of a wireless blood pressure monitor and an app in combination with an integrated preeclampsia symptom checklist. Study design: Prospective observational study with 14 pregnant women during a 15 weekday study period. For feasibility purposes, compliance was measured by evaluating the number of entered BP and symptom checklists. Comparing all the entered values with the threshold values checked the accuracy of the automatic alerts. Usability and patient satisfaction were measured using questionnaires. Results: Compliance rates for blood pressure and symptom checklist were 93% and 85% respectively. No false positive or missing alerts were found in the alarm system. The telemonitoring system alarmed 7 times for BP thresholds (3.8% of all received values), Of 167 returned symptom checklists, 93% of symptom alarms could be handled with expectant management because of concurrent normal blood pressure. The majority of participants were satisfied with the system. Conclusions: This is the first feasibility study of a telemonitoring platform, combining remote monitoring of BP with preeclampsia symptoms in pregnancy care. Action from health care providers during telemonitoring is only needed in case of alarming combinations of results. This system is potentially very useful in care for women at risk for hypertensive disorders during pregnancy.